2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.23712
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Learning Outcomes and Content Mastery in Online and Face-to-Face Engineering Statics Courses

Abstract: Online engineering education has expanded rapidly in recent years and many questions have been raised about the learning outcomes and content mastery in online classes as they compare with traditional face-to-face formats. This paper compares the learning outcomes and content mastery for students in an Engineering Mechanics (Statics) course taught in three different modes of instruction. This study was initiated in 2011 with a cohort of three courses: one taught asynchronously online, one taught face-to-face, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
3
7
0
Order By: Relevance
“…In addition, it is shown that non-completion rates are higher in online group versus in-person group. Finally, similar conclusions were provided in works by Douglas [4] and Marriott [5] for students in Engineering Mechanics course and in two Computer Science courses respectively. Additionally, Douglas [4] also highlights that online students were less satisfied with the delivery mode compared with in-person students.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, it is shown that non-completion rates are higher in online group versus in-person group. Finally, similar conclusions were provided in works by Douglas [4] and Marriott [5] for students in Engineering Mechanics course and in two Computer Science courses respectively. Additionally, Douglas [4] also highlights that online students were less satisfied with the delivery mode compared with in-person students.…”
Section: Introductionsupporting
confidence: 82%
“…In addition, research presented by Ssemakula [2] provides the same observation on learning effectiveness for Engineering Economic Analysis course. Next, findings by Kozak [3] and Douglas [4] show that online students in two mechanics classes performed equally or outperformed in-person group. Similar results are demonstrated by Marriott [5] for two Computer Science courses intended for freshmen, juniors and seniors.…”
Section: Introductionmentioning
confidence: 83%
“…However, they found out that the students perceived the online portion/format to be more difficult and challenging. Douglas (2015) found out for an engineering statics course that "there was little to no difference in content mastery between students who completed the online and face-to-face sections of the class". This includes score on identical proctored exam problems.…”
Section: Introductionmentioning
confidence: 99%
“…Literature is abound by successful transitions that satisfy diverse student needs and successfully achieve the learning outcomes [2,6,[8][9][10]. Most document broad strategies for developing online content [11].…”
Section: Introductionmentioning
confidence: 99%